Truancy Behavior Student in terms of Factors Causing and Teacher's Efforts to Overcome Them - Elva Betti Idris; Yarmis Syukur (Universitas Negeri Padang, 2021)
This research is motivated by the phenomenon of students who often skip class without clear information, being around the school while sitting in the canteen during class hours. This is because students are not interested in lessons and are bored in learning. This study aims to describe truancy behavior in terms of the causes and teachers' efforts to overcome it.This type of research is descriptive using quantitative methods. The population of this study was 278 students of SMPN 34 Padang who were registered in the 2019/2020 school year, with a total sample of 54 students who were truant, the sample selection used a purposive sampling technique. The data collection technique used a questionnaire with a Likert scale model. Data were analyzed using descriptive statistical techniques. This study describes the factors that cause truant students to be in the low category, and based on the indicators (1) the students' own factors are in the high enough category with a percentage (38.89%), (2) family factors are in the low category with a percentage (55, 56%), (3) school factors are in the low category with a percentage (37.04%), and community factors in the school environment are in the high enough category with a percentage (44.44%). Furthermore, the teacher's efforts to overcome truant students are in the high enough category, and based on the indicators (1) enforcing school discipline is in the very high category with a percentage (37.04%), (2) helping to overcome problems experienced by students is in the high category with a percentage (35.19%), (3) providing facilities, learning facilities and infrastructure is in the high enough category with a percentage (42.59%), and (4) establishing cooperation with various parties is in the high enough category with a percentage ( 53.70%).